A novel colour image watermarking scheme based on Schur decomposition. (24th February 2020) - Su, Qingtang; Su, Lin; Wang, Gang; Li, Leida; Ning, Jianting
A novel colour image watermarking scheme based on Schur decomposition is proposed in this paper. By analysing the 3 × 3 unitary matrix U via Schur decomposition, the strong similarity relation between U 2, 1 and U 3, 1 is found. This relation will represent one kind of embedded watermark information, i.e., '1' or '0', and will be used to extract watermark from 3 × 3 unitary matrix U in the blind manner. Moreover, the proposed method requires lower computational complexity than other methods based on singular value decomposition (SVD) since Schur decomposition is only an intermediate step in SVD decomposition. In addition, the proposed method does not have the false-positive detection problem like that based on SVD. The experimental results show that the proposed scheme has better performance in terms of invisibility, robustness, capacity and real-time feature.